Avoiding Digital Divide in European Union through European Green Deal - Brătucu, G.; Nichifor, E.; Sumedrea, S.; Chițu, I.B.; Lixăndroiu, R.C. (Amfiteatru Economic)
The digital society is threatened by the existing divide that seems to be deepening between the population that has access to information technology and the population that for some reason does not. The phenomenon of digital divide has become a very important issue in the process of transformation of society and the authors relate it to European Green Deal, in order to identify the determinants and ways to reduce the negative effects that will be eliminated according to the proposed schedule. For this purpose, a narrative review of the literature was used as a research method, corroborated with a multidimensional analysis of the data regarding the Internet access in the households from the member countries of the European Union. As a result, eight determinants of the digital divide were identified, along with four examples of how they can be addressed. According to the authors, the Deal, which has committed all 27 member states to create new opportunities for innovation, investment, and jobs, can support the positive transformation of European society, even against a backdrop of enormous challenges and huge impacts that we can now imagine